Is TB Testing Associated With Increased Blood Interferon-Gamma Levels? - Kennedy, Aideen E.; O’Mahony, Jim; Byrne, Noel; MacSharry, John; Sayers, Riona G. (Frontiers in Veterinary Science, 2017)
The Republic of Ireland reports a relatively low prevalence of Johne’s disease (JD) compared to international counterparts. Postulated reasons for this include a lower average herd size and a grass-based production system. Ireland also engages in high levels of bovine tuberculosis (bTB) testing. As interferon-gamma (IFN-γ) is believed to play a key role in protecting against JD, it is our hypothesis that administration of purified protein derivative (PPD), as part of the bTB test, is associated with a systemic increase in IFN-γ production which may potentially limit clinical progression of the disease. We studied 265 cows (202 Friesian and 63 ‘Non-Friesian’ e.g. JerseyX, Norwegian Red) to assess IFN-γ levels and Mycobacterium avium subspecies paratuberculosis (MAP) antibody response before and after the bTB test. As part of the compulsory annual bTB test, avian and bovine PPD were administered at two separate cervical sites. To assess IFN-γ production, blood samples were taken before and 72 hours after PPD administration. MAP antibody response was assessed before and 10 days post PPD administration. A significant increase in MAP antibody response was identified post- bTB compared to pre-bTB response (P<0.001). Additionally, IFN-γ production significantly increased at the post- bTB time point (p<0.001) compared to the pre-bTB test readings. This may indicate a beneficial effect of bTB testing in controlling JD.